A comparative study of different methods of processing aortic homografts. Issue 6 (November 1969) - Welch, W.
Abstract : Segments of the same aortic cusp were processed in different ways and compared from a histological and histochemical point of view with a non-processed segment. Changes produced by certain methods of processing bear a resemblance to the changes noted in the normal ageing process of the aortic valves. These changes are commented upon; but further experimental work is necessary to determine which method of processing aortic homografts gives the best long-term results.